A psychometric user experience model based on fuzzy measure approaches. (October 2018) - Chou, Jyh-Rong
Highlights: This paper presents a psychometric user experience model using fuzzy measure approaches. The User Experience Questionnaire (UEQ) is employed as a psychometric instrument to collect respondents' rating data. Rating variables are converted into Gaussian fuzzy numbers and aggregated by means of the aggregation operations. A user experience index (UXI) was developed as a metric for assessing UX quality quantitatively. An empirical study concerning the episodic UX measures of using a set of touch mice was conducted. Abstract: User experience (UX) is considered a key quality of interactive products in today's competitive mass markets and is of growing interest in both academia and industry. UX concerns the encounters a user has while interacting with products, systems, and services. It is ubiquitous, omnipresent, and dynamic in nature, referring to the non-quantifiable, subjective, affective-based, and context-dependent processes. UX is difficult for researchers to objectively and uniformly measure as it involves complex human perceptual interpretations of experiential responses with a certain degree of uncertainty, imprecision, and vagueness. Based on the user experience questionnaire (UEQ), this paper presents a psychometric UX model using fuzzy measure approaches, the purpose of which is to develop a metric for quantitative assessment of certain product UXs through a user experience index (UXI). This model enables researchers to understand users' perceptions of the interactions that constitute qualities of using a specific product. An empirical study concerning the episodic UX measures of using a set of touch mice was conducted to verify the applicability and effectiveness of the proposed UX model. The theoretical and practical implications of the UX model are also discussed.